2005
DOI: 10.1016/j.febslet.2005.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Fractal nature of chromatin organization in interphase chicken erythrocyte nuclei: DNA structure exhibits biphasic fractal properties

Abstract: Arrangement of chromatin in intact chicken erythrocyte nuclei was investigated by small angle neutron scattering. The scattering spectra have revealed that on the scales between 15 nm and 1.5 lm the interior of the nucleus exhibited properties of a mass fractal. The fractal dimension of the protein component of cell nucleus held constant at approximately 2.5, while the DNA organization was biphasic, with the fractal dimension slightly higher than 2 on the scales smaller than 300 nm and approaching 3 on the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 14 publications
8
61
0
3
Order By: Relevance
“…How this is achieved has been revealed by the seminal simulation studies of the collapse of a linear polymer by Grosberg et al [57], which show how a compact "crumpled globule" with fractal properties is formed (a notable example of the value of non-translational research). Experiments and simulations strongly support this fractal manner of packing chromatin in the nucleus [58][59][60][61] (with the exception of yeast), which was suggested earlier by neutron diffraction studies of nuclei [62]. Data from 3C studies of human chromosomes are consistent with a fractal organization, but not with the alternative "equilibrium globule" conformation [58].…”
Section: Packing the Genome Into The Nucleussupporting
confidence: 64%
“…How this is achieved has been revealed by the seminal simulation studies of the collapse of a linear polymer by Grosberg et al [57], which show how a compact "crumpled globule" with fractal properties is formed (a notable example of the value of non-translational research). Experiments and simulations strongly support this fractal manner of packing chromatin in the nucleus [58][59][60][61] (with the exception of yeast), which was suggested earlier by neutron diffraction studies of nuclei [62]. Data from 3C studies of human chromosomes are consistent with a fractal organization, but not with the alternative "equilibrium globule" conformation [58].…”
Section: Packing the Genome Into The Nucleussupporting
confidence: 64%
“…(17)- (19). They can be used to fit experimental SAS data and distinguish between the type I system (one fractal absorbs the other fractal) and the type II system (nonoverlapping fractals) as described in Sec.…”
Section: Discussionmentioning
confidence: 99%
“…where we put by definition (19) and the exponents τ 1 and τ 2 are related to the corresponding fractal dimensions by Eq. (1).…”
Section: The Interpolating Formula and The Generalized Methods Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in vitro studies using texture analysis of microscopy images have shown that the topology of chromatin is well represented as a fractal media (12). Likewise, ex vivo analysis of somatic copy number alterations and neutron scattering measurements of isolated nuclei have shown that, across these length scales, chromatin is well described as a fractal media (13)(14)(15). In conjunction, molecular techniques such as chromosomal capture methods [chromosome conformation capture (3C) and high-throughput 3C (Hi-C)] have shown that the higher-order organization of chromatin above single nucleosomes and below the structure of chromosomal territories follows this same power-law fractal organization.…”
Section: Significancementioning
confidence: 99%